2006
DOI: 10.1128/jvi.00779-06
|View full text |Cite
|
Sign up to set email alerts
|

A Helper-Dependent Capsid-Modified Adenovirus Vector Expressing Adeno-Associated Virus Rep78 Mediates Site-Specific Integration of a 27-Kilobase Transgene Cassette

Abstract: Random integration of viral gene therapy vectors and subsequent activation or disruption of cellular genes poses safety risks. Major efforts in the field are aimed toward targeting vector integration to specific sites in the host genome. The adeno-associated virus (AAV) Rep78 protein is able to target AAV integration to a specific site on human chromosome 19, called AAVS1. We studied whether this ability could be harnessed to achieve site-specific integration of a 27-kb transgene cassette into a model cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 38 publications
(41 reference statements)
1
50
1
Order By: Relevance
“…Our group is specifically interested in targeting transgene expression cassettes to specific sites in the genome of human hematopoietic stem cells (HSCs) by transient expression of proteins with site-specific endonuclease activity, such as the AAV Rep78 protein [1] and sequence-specific zinc-finger nucleases [2]. Gene transfer into HSCs by transfection or electroporation is hampered by low efficiency and high cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Our group is specifically interested in targeting transgene expression cassettes to specific sites in the genome of human hematopoietic stem cells (HSCs) by transient expression of proteins with site-specific endonuclease activity, such as the AAV Rep78 protein [1] and sequence-specific zinc-finger nucleases [2]. Gene transfer into HSCs by transfection or electroporation is hampered by low efficiency and high cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, GFP expression from the AAVS1 site was significantly higher than expression from other sites. 55 However, with the experiments conducted in our studies, it was not possible to determine the cause of the different b-gal activities observed.…”
Section: Integration Of 100 Kb Gene Via Hsv/aav Amplicon Vector a Oehmentioning
confidence: 67%
“…However, in the rep-plus BGAL clones detection of green fluorescence or rep-sequences could also be explained by site-specific integrations mediated by the p5IEE in rep. Additionally, recent analysis with Ad/AAV vector, containing a 27 kb globin-LCR-GFP transgene also revealed recombination of the transgene into the genomic globin LCR site in 25% of the clones. 55 In gene therapy, homologous recombination of an introduced transgene with the endogenous gene can correct a mutation in the gene through replacement with the wild-type sequence. The possibility of homologous recombination between the transduced and the endogenous BGAL sequences was not assessed in this study but will be a crucial point in future studies.…”
Section: Integration Of 100 Kb Gene Via Hsv/aav Amplicon Vector a Oehmentioning
confidence: 99%
“…This integration occurs preferentially into a specific site of the q arm of chromosome 19 (AAVS1) in a Rep-dependent manner (Kotin et al, 1990;Kotin et al, 1991;Samulski et al, 1991;McCarty et al, 2004;Philpott et al, 2004;Wang and Lieber, 2006). Specific integration sites for the other AAV serotypes have not yet been identified.…”
Section: Adeno-associated Virus Biology and Trafficking In Host Cellsmentioning
confidence: 99%
“…some not yet identified cellular DNA repair mechanism (reviewed in Stender et al, 2007). These dsDNA intermediates integrate into a specific site of human chromosome 19 (19q13.3q-ter) called AAVS1 (Kotin et al, 1990;Kotin et al, 1991;Samulski et al, 1991;McCarty et al, 2004;Philpott et al, 2004;Wang and Lieber, 2006). In the absence of a co-infection by a helper virus (commonly adenovirus or herpesvirus), the integrated AAV genome remains in a latent state.…”
Section: Viral Systemsmentioning
confidence: 99%